British weather and the climate of enlightenment - Golinski, Jan (University of Chicago Press, 2007)
Enlightenment inquiries into the weather sought to impose order on a force that had the power to alter human life and social conditions. British Weather and the Climate of Enlightenment reveals how a new sense of the national climate emerged in the eighteenth century from the systematic recording of the weather, and how it was deployed in discussions of the health and welfare of the population. Enlightened intellectuals hailed climate's role in the development of civilization but acknowledged that human existence depended on natural forces that would never submit to rational control. Reading th.